Lemma(re)konstruktion i K.F. Söderwalls Ordbok öfver svenska medeltids-språket - Djärv, Ulrika (LexicoNordica, 2006)
My ongoing study of K.F. Söderwalls period dictionary Ordbok öfver svenska medeltids- språket (Sdw) (1884–1918, 1925–1973) concerns, among other things, the reconstruction of the lexicographers principles for constructing lemmas from the Old Swedish material, which is rich in variation. It has been claimed that the lemmas in Sdw are constructed to represent an Early Old Swedish form. My observations, presented here, of the lexicographers handling of vowel balance and consonant epenthesis indicate that the constructed lemmas are normalized towards a somewhat younger Late Old Swedish form. However, other details in the lemmas suggest otherwise, and this inconsistent lexicographical adoption of neogrammarian soundlaws can cause difficulties in using Sdw. The article also touches upon the possibilities of using frequency and sociolinguistically motivated prestige forms as principles for constructing lemmas in historical dictionaries.